Validation of the generalized anxiety disorder screener (GAD-7) in Cypriot pregnant and postpartum women - Paris Vogazianos; Emma Motrico; Sara Domínguez-Salas; Andri Christoforou; Eleni Hadjigeorgiou (BMC, 2022)
Abstract Background Anxiety is increasingly acknowledged as a common mental health issue during the perinatal period. Its prevalence as well as the associated adverse effects constitute screening imperative. This study evaluates the psychometric properties and underlying factor structures of a Greek version of GAD-7 among pregnant and postpartum women (up to 6 months) in Cyprus. Methods This study was conducted from June to December 2020. A total of 457 Cypriot women in the perinatal period (222 pregnant and 235 postpartum) were surveyed. The assessment included anxiety (GAD-7) and depression (EPDS), and psychosocial factors related with anxiety. The internal consistency and factor structure of GAD-7 were evaluated using reliability coefficients, Cronbach's Alpha and McDonald's Omega, and factor analysis, both Exploratory as well as Confirmatory. Results GAD-7 demonstrated good internal consistency (α = 0.907; Ω = 0.909). Horn's parallel analysis indicated a single factor as the most appropriate. CFA using the standard ML method indicated a good model fit, χ2 = 21.207, p = 0.096; CFI = 0.999; SRMR = 0.027. More studies are needed to determinate the cut-off point and the maximisation of the scale's sensitivity and specificity in pregnant and postpartum Greek Cypriot women. Conclusions GAD-7 is a valid and reliable measure and healthcare professionals should utilize GAD-7 as a standard instrument for the screening of anxiety symptoms in pregnant and postpartum Greek Cypriot women.